Inhibition of COX‐2‐mediated eicosanoid production plays a major role in the anti‐inflammatory effects of the endocannabinoid N‐docosahexaenoylethanolamine (DHEA) in macrophages. (23rd September 2014) - Meijerink, Jocelijn; Poland, Mieke; Balvers, Michiel G J; Plastina, Pierluigi; Lute, Carolien; Dwarkasing, Jvalini; van Norren, Klaske; Witkamp, Renger F
<x xml:space="preserve">Abstract</x> Background and Purpose N‐docosahexaenoylethanolamine (DHEA) is the ethanolamine conjugate of the long‐chain polyunsaturated n‐3 fatty acid docosahexaenoic (DHA; 22: 6n‐3). Its concentration in animal tissues and human plasma increases when diets rich in fish or krill oil are consumed. DHEA displays anti‐inflammatory properties in vitro and was found to be released during an inflammatory response in mice. Here, we further examine possible targets involved in the immune‐modulating effects of DHEA. Experimental Approach Antagonists for cannabinoid (CB)1 and CB2 receptors and PPARγ were used to explore effects of DHEA on NO release by LPS‐stimulated RAW264.7 cells. The possible involvement of CB2 receptors was studied by comparing effects in LPS‐stimulated peritoneal macrophages obtained from CB2−/− and CB2+/+ mice. Effects on NF‐κB activation were determined using a reporter cell line. To study DHEA effects on COX‐2 and lipoxygenase activity, 21 different eicosanoids produced by LPS‐stimulated RAW264.7 cells were quantified by LC‐MS/MS. Finally, effects on mRNA expression profiles were analysed using gene arrays followed by Ingenuity® Pathways Analysis. Key Results CB1 and CB2 receptors or PPARs were not involved in the effects of DHEA on NO release. NF‐κB and IFN‐β, key elements of the myeloid differentiation primary response protein D88 (MyD88)‐dependent and MyD88‐independent pathways were not decreased. By contrast, DHEA significantly reduced levels of several COX‐2‐derived eicosanoids. Gene expression analysis provided support for an effect on COX–2‐mediated pathways. Conclusions and Implications Our findings suggest that the anti‐inflammatory effects of DHEA in macrophages predominantly take place via inhibition of eicosanoids produced through COX‐2. Linked Articles This article is part of a themed section on Cannabinoids 2013 published in volume 171 issue 6. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.2014.171.issue-6/issuetoc